Synthesis, structure and density functional theory calculations of a novel photoluminescent trisarylborane–bismuth(III) complex. (28th June 2019) - Amarne, Hazem; Helal, Wissam; Wang, Suning
Abstract: A novel trisarylborane–Bi(III) complex, tris(4‐(dimesitylboryl)phenyl)bismuthine [Bi(PhBMes2 )3 ], in which (Ph = phenyl, and Mes = mesityl), was synthesized via the reaction of bismuth (III) chloride (BiCl3 ) with three equivalents of lithiated (4‐bromophenyl)‐ dimesitylborane [BrPhBMes2 ]. The new trisarylbismuthine was characterized by elemental analysis, ultraviolet–visible (UV–vis) spectroscopy, and NMR ( 1 H and 13 C) spectroscopy. The molecular structure of Bi(PhBMes2 )3 in the solid state was determined using single‐crystal X‐ray diffraction analysis, which showed short intermolecular C–H···H–C contact. The complex is a fluorescent emitter (λmax = 395 nm) at room temperature and a phosphorescent emitter (λmax = 423 nm) at 77 K, which displayed a long lifetime of 495 ms. The UV–vis transitions were investigated using density function theory (DFT) and time‐dependent (TD)‐DFT calculations. Natural bond orbital analysis showed that the bismuth (III) center was mainly Lewis acidic in nature.